Culturally responsive pedagogy in support of Roma students: perspectives from Bulgaria - Veselina S. Lambrev (Education Inquiry)
Across Europe, anti-Roma sentiments and practices in education have hindered the inclusion of Roma people. Using the theoretical lens of culturally responsive teaching, this study examined Bulgarian teachers’ cultural awareness and the pedagogical strategies they employ to support Roma students. Interview data from 14 teachers were conducted at two high schools with predominantly Roma student populations. The analysis revealed that teachers believed in the importance of continuously building cultural awareness through learning about the unique culture and experiences of Roma students and through building trusting relationships with students and their families. The educators reported gaining cultural knowledge through their own research and highlighted the lack of formal culturally responsive teacher training. Teachers acknowledged the negative impact of poverty and discrimination on Roma children’s academic success but failed to build critical consciousness that recognises the harmful effect of school segregation. The study makes implications for the need to support educators in post-socialist contexts to engage in critical self-reflection to challenge existing dominant discourses and power relations which may limit teachers’ views of Roma communities.